Comparative study of ethanol and isobutanol as gasoline blend for internal combustion engine / Mohd Nur Ashraf Mohd Yusoff - Mohd Nur Ashraf, Mohd Yusoff (2018)
The heavy reliance on petroleum-derived fuels such as gasoline in the transportation sector is one of the major causes of environmental pollution. For this reason, there is a critical need to develop cleaner alternative fuels. The alcohols such as ethanol and isobutanol can be blended with gasoline to produce cleaner alternative fuels because of their favorable physicochemical properties. This study examined the effect of single and dual alcohol of ethanol and isobutanol in gasoline blends on the engine performance and emission characteristics of a spark ignition engine. Six types of fuel blends consist of both alcohols were mixed with unleaded gasoline at different volume rates (E10, E20, iB10, iB20, E5iB5 and E10iB10) and the physicochemical properties of these blends are measured and compared with the pure gasoline. Tests are conducted on a SI engine at wide open throttle position by varying the engine speed ranging from 1000 to 5000 rpm with step of 1000 rpm. Then, a constant- speed test was conducted at 4000 rpm by varying engine torque ranging from 20 to 100 Nm with step of 20 Nm The results show that the fuel blends have a significant increase in the density, viscosity and heat of vaporization, but they are lower in heating value and Reid vapor pressure as compared with pure gasoline. In addition, the E20 blend gives the most significant enhancement for torque, brake power and brake thermal efficiency with an average enhancement of 3.88, 2.60 and 13.61%, respectively, while E10iB10 blend gives the largest improvement of brake specific fuel consumption with an average enhancement of 5.77% than that of pure gasoline. There are no significant changes of exhaust gas temperature between the fuel blends and pure gasoline for both operating conditions. In terms of exhaust emissions, E10iB10 blend results in the lowest CO and HC emissions by varying the engine speeds with an average reduction of 11.21 and 17.13%, respectively, relative to pure gasoline.By varying the engine torque, E20 and E10iB10 blends result in the lowest CO and HC emissions with an average reduction of 44.02 and 46.32%, respectively, with respect to pure gasoline. However, all the tested fuel blends show higher CO2 emissions as compared to pure gasoline for both operating conditions. In terms of NOX emission, there is no significant differences for all fuel blends with pure gasoline for both conditions.